The Effect of Implementing Financial Accounting Standards Statement No. 71 on Earnings Management and Financial Instruments in Banking Companies Listed on the IDX (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the impact of the implementation of Financial Accounting Standard Statement (PSAK) No. 71 on earnings management in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2023 period. The study uses a quantitative approach, with secondary data collected from the financial statements of 43 banking companies listed on the IDX. A sample of 39 banks and 78 data observations collected over two years was used for the analysis. The data collection method involved gathering written sources from the financial reports of the selected banks. The analysis was conducted using multiple linear regression, with the results revealing that PSAK No. 71 negatively impacts earnings management in these banks. Specifically, the implementation of PSAK No. 71 affects the way banks recognize and measure financial instruments, leading to a reduction in the manipulation of earnings. This suggests that the standard plays a significant role in improving transparency and reliability in financial reporting within the banking sector. The findings highlight the effectiveness of PSAK No. 71 in curbing earnings management practices, contributing to more accurate financial statements. The study's results underscore the importance of implementing accounting standards that promote fair and transparent financial reporting, benefiting stakeholders and ensuring financial stability in the banking sector